Cane Hay Cost-Return Budget in Western Kansas - Ibendahl, Gregg; O'Brien, Daniel M.; Holman, John; Haag, Lucas (My University, 2015)
This publication estimates the costs and returns associated with a typical sorghum sudangrass hybrid planted at heavier seeding rates and harvested as a hay crop in western Kansas.
MF997_2015_04
Keywords: MF997; Economics; Crops; MF